Identifying the determinants for developing of smart city initiatives in delivering convenience and safety to local community - Tan, Tze Horng; Adam Assim, Mohd Ibrani Shahrimin; Chong, Kim Mee; Lai, Hon Kuan (Human Resource Management Academic Research Society, 2021)
Cities in Malaysia are facing rapid urbanisation in the last decades and common issues faced by these cities include traffic congestion, environment pollution, security and deterioration of natural resources. Smart cities, in global context, are introduces as solutions to the urban issues. For Malaysia, smart cities are a new approach in urban management and development to make the cities more sustainable and liveable. This study analyses many of these challenges, in developing the smart city initiatives in the local context, offering a valuable insight of the relevant key literature, and a foundation for the development of smart city initiatives blueprint. The objectives of the study are to ascertain the determinants for developing of smart city initiatives and identify the level of importance for these initiatives from the local community perspectives. The study includes 20 items in the smart city initiatives such as public safety, public convenience, residents’ participation, communication and information, urban mobility (transportation), wastewater treatment, smart payment and finance, garbage collection services, neighbourhood maintenance / cleaning services, CCTVs monitoring system (traffic monitoring) and so forth. This is an online survey and a total of 533 valid responses are received from the questionnaires which are presented in three languages and were analysed using IBM Statistical Package for the Social Sciences (SPSS). The data are first analysed for reliability and validity and the determinants’ mean and variance are calculated for significant comparison purposes. The findings clearly indicate that the most important determinant in Miri’s Smart City initiatives is the garbage collection services which reflect the local community’s concerns for the quality of life and the public community services in the neighbourhood.